2021
DOI: 10.1002/dad2.12219
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in Brazilians with mild cognitive impairment and dementia

Abstract: Introduction Knowledge is limited about behavioral and psychological symptoms of mild cognitive impairment (MCI) and dementia in racial and ethnic minorities. Methods As part of the Pathology, Alzheimer's and Related Dementias Study (PARDoS), we interviewed knowledgeable informants of 2319 older Brazilian decedents (67% white, 11% black, 22% mixed) using the informant portion of the Clinical Dementia Rating Scale to classify MCI and dementia and the Neuropsychiatric Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Wilson and colleagues (2021) analyzed data from the Pathology, Alzheimer’s and Related Dementias Study (PAR-DoS). 35 The sample consisted of informants of 2319 older Brazilian decedents who were enrolled in PAR-DoS. These participants were 65 years of age or older at time of death.…”
Section: Resultsmentioning
confidence: 99%
“…Wilson and colleagues (2021) analyzed data from the Pathology, Alzheimer’s and Related Dementias Study (PAR-DoS). 35 The sample consisted of informants of 2319 older Brazilian decedents who were enrolled in PAR-DoS. These participants were 65 years of age or older at time of death.…”
Section: Resultsmentioning
confidence: 99%
“…mentioned our paper, we were surprised by what we believe to be misrepresentation of our results, when they attest that their findings showing differences in behavioral and psychological symptoms between cognitively normal and MCI groups are novel. In the Discussion section, the authors described our study and compared their findings to ours, 3 which we quote here: "One previous study examined these associations in older Brazilian decedents. 12 The researchers reported that behavioral and psychological symptoms were elevated in those with dementia compared to those without cognitive impairment, but symptoms in the MCI subgroup did not differ from the no cognitive impairment subgroup.…”
Section: Neuropsychiatric Symptoms In Community-dwelling Older Brazil...mentioning
confidence: 92%
“…We agree that Nunes et al., 1 found elevations in mild cognitive impairment on 7 of 12 Neuropsychiatric Inventory items. The study by Wilson et al., 2 was built on the prior literature including Nunes et al., 2 by deriving composite measures of behavioral and psychological symptoms from the Neuropsychiatric Inventory and using these as outcomes instead of individual Neuropsychiatric Inventory items, thereby likely minimizing measurement error. With these composite measures, we were able to show that mild cognitive impairment is characterized by a global (rather than a selective) elevation in neuropsychiatric symptoms.…”
mentioning
confidence: 99%